Ferns and lycophytes: an ethnobotany review for Brazil - Modena de Medeiros, Caroline; Ritter, Mara Rejane; Gonzatti, Felipe (Ethnobotany Research and Applications, 2023)
Background: Ferns and lycophytes comprise all vascular plants with no flowers, fruits, or seeds, grouped under the artificial name Pteridophytes. This group presents a broad range of ethnobotanical uses, being those medicinal, ornamental, ritual, edible, or others, but there are few studies that register the uses of this specific group and no comprehensive gathering of this data under one study in Brazil. This review aimed to gather, analyze, and organize existing data on the historical and present ethnobotany of Pteridophytes in Brazil. Methods: This study was conducted through a literature review, regarding historical and current data in order to understand how the human populations in Brazil utilize these plants. Species were also updated when necessary to generate a taxonomic correct listing. Results: We gathered data regarding 367 species, within 702 valid citations in 124 different sources, dating from the 16th century until today. Another 118 imprecise citations were registered, making up to a total of 820 species’ citations. The most reported uses were medicinal and ornamental, followed by those of ritual and food uses. Almost all Pteridophyte families have recorded uses, and the species are used in all regions of the country, by diverse human groups. Conclusion: This survey brings to surface the broad use of Pteridophyte species in the country, compiling this information in an unprecedented way for Brazil, and highlighting their importance for human groups. Keywords: brazilian flora; brazilian biodiversity; useful plants; traditional knowledge.